PENGEMBANGAN MEDIA PEMBELAJARAN ULAR TANGGA UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS 4 SEKOLAH DASAR - Nur Hapipih (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This research is expected to be able to determine the level of students' learning motivation through learning media of snakes and ladders towards science learning. This research is a study that uses qualitative and quantitative methods using a sample of 32 elementary school students. The data collection technique in this studywas to use a questionnaire and document the results of students' learning motivationwhen using snakes and ladders learning media. The implementation of this research takes place in the elementary school of SDN Pasirsari 03. The method used in this research is the ADDIE method. Learning media snakes and ladders can be categorized as valid or can increase student motivation because it gets an average score of 88.6% in this study.